2022
DOI: 10.26858/est.v8i2.38693
|View full text |Cite
|
Sign up to set email alerts
|

Development of Social Science Textbooks Integrated with Islamic and Local Culture Values

Abstract: Social Science textbooks tend to be less dynamic and integrative with Islamic values and local culture. This research is aimed to compose an integrated social science learning textbook which is valid, practical, and effective in improving students’ nationalism character. Type of research and development (R&D) with 4D model procedures (define, design, develop and disseminate) to fulfill the procedure of development. The developed textbook that fulfills scientists’ validity result and its practical use as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The elements of local wisdom can provide contextualized student learning experiences [30,31]. It helps students understand how learning can be applied in their daily lives so that learning becomes more meaningful and relevant in connecting theory with practice in everyday life [32]. In local wisdom-based learning, students learn practical skills that can be applied in everyday life, such as technology, leadership, presentation, and time management skills [29,32,34,[73][74][75].…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elements of local wisdom can provide contextualized student learning experiences [30,31]. It helps students understand how learning can be applied in their daily lives so that learning becomes more meaningful and relevant in connecting theory with practice in everyday life [32]. In local wisdom-based learning, students learn practical skills that can be applied in everyday life, such as technology, leadership, presentation, and time management skills [29,32,34,[73][74][75].…”
Section: B Discussionmentioning
confidence: 99%
“…Furthermore, it is also essential to integrate educational films with other learning methods and strategies to achieve optimal learning outcomes, such as integrating with local wisdom to improve students" Arabic communication skills. It makes learning more relevant, strengthens students" sense of identity, reduces the loss of cultural identity in an increasingly globalized society, and makes it easier for students to connect theory with practice in everyday life [32] so that learning Arabic Communication Skills is more fun and effective.…”
Section: Educational Filmsmentioning
confidence: 99%
“…One way that can be done in introducing local wisdom to students is by integrating it into emodules as attractive tools and facilities that facilitate students' attention while studying. The existence of e-modules based on local wisdom is closely related to learning biology which is a subject that is closely related to the environment (Latri, 2022). Hadi & Dazrullisa (2018) revealed that teaching materials are said to be good if they are developed and designed according to the characteristics according to the needs of students by looking at geographical, ethnographic, and regional wealth factors.…”
Section: Introductionmentioning
confidence: 99%